Population genetic structures of Puccinia triticina in five provinces of China - Yutong Ma; Taiguo Liu; Bo Liu; Li Gao; Wanquan Chen (European Journal of Plant Pathology, 2020)
To understand the evolution of Puccinia triticina , we used single nucleotide polymorphisms (SNPs) to evaluate the P. triticina population genetic structure in five Chinese provinces, Gansu, Henan, Hubei, Shaanxi and Sichuan from 2013 to 2015. The populations exhibited characteristics of high haplotype diversity but low nuclear diversity. The gene flow was frequent between Gansu and Henan, Gansu and Sichuan and Sichuan and Henan. Genetic differentiation was significant among populations except between Henan and Gansu and between Henan and Sichuan ( P < 0.05 ). The P. triticina isolates from the five provinces were grouped into two clusters: Gansu/Henan/Shaanxi/Sichuan and Hubei clusters. AMOVA analysis showed that the populations exhibited genetic variation; the variation percentage reached 87.45%, and the genetic variation within populations was the major source of variation. Our results suggest that the genetic diversity of P. triticina was high and that gene flow was frequent between populations. P. triticina population of China had experienced a rapid expansion, which caused some differences between populations. The Hubei population was different from other population due to genetic variation within populations.